Riss / Lücke / Scharnier A : Rift / Gap / Hinge A. - Bellenbaum, Rainer; Buchmann, Sabeth; Dunst, Heinrich; Pamminger, Walter (Zürich : Verlag Scheidegger & Spiess AG, 2010)
Baldessari, John ; Bayer, Konrad ; Broodthaers, Marcel ; Bujnowski, Rafal ; Caramelle, Ernst ; Clegg & Guttmann ; Dunst, Heinrich ; Ganahl, Rainer ; Gansterer, Nikolaus ; Lawler, Louise ; Mancuska, Jan ; Marclay, Christian ; Riedel, Michael S. ; Schmatz, Ferdinand ; Tscherkassky, Peter ; Tuerlinckx, Joëlle ; Zaugg, Rémy
Duits
Engels
Tentoonstelling ' Riss/Lücke/Scharnier A - Rift/ Gap/ Hinge A', Galerie nächtst St.Stephan Rosemarie Schwarzwälder, Wien, 24.11.2006 - 19.02.2007.
boek